The reliability and validity of the European League Against Rheumatism Sjögren Syndrome Patient Reported Index in patients with primary Sjögren syndrome: A Turkish version study - Elif Gür Kabul,; Aylin Keskin,; Pervin Demir,; Bilge Başakcı Çalık,; Veli Çobankara, (Archives of Rheumatology, 2021)
Objectives: This study aims to assess the reliability and validity of the Turkish version of the European League Against Rheumatism (EULAR) Sjögren Syndrome Patient Reported Index (ESSPRI) (TR) in patients with primary Sjögren syndrome (pSS). Materials and methods: A cross-sectional survey study design and analysis were used to assess the reliability and validity of the ESSPRI (TR) between March 2019 and July 2019. A total of 30 patients (5 males, 25 females; mean age 54.1±10.5 years; range, 18 to 75 years) diagnosed as pSS according to revised American College of Rheumatology (ACR)/EULAR classification criteria were included. ESSPRI (TR) was applied to the patients with face-to-face interviews twice: on their first visit and after an interval of 15 days. The test-retest reliability was assessed with the intraclass correlation coefficient (ICC), and the internal consistency of the multi-item subscales by calculating Cronbach alpha values. The correlations between basal and stimulated salivary flow (BSF and SSF), Oral Health Impact Profile-14 (OHIP-14) and Oral Health-Related Quality of Life-UK (OHRQOL-UK) questionnaires were evaluated to determine the construct validity. Results: The ICC value for the test/retest reliability of ESSPRI (TR) was 0.925. The internal consistency was 0.682. There were low to moderate correlations between the ESSPRI (TR) total score and BSF (-0.39), SSF (-0.50), OHIP-14 total (0.57) and OHRQOL-UK total (-0.67). Conclusion: The Turkish version of the ESSPRI was found to be clinically valid and reliable to be used in clinical evaluations and rehabilitation interventions in patients with pSS.